Pengaruh Perceived Usefulness Dan Kemudahan Penggunaan Terhadap Kepuasan Konsumen E-Toll : (Studi Pada Pengguna E-Toll Card Di Cirebon) (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
Technological advances aim to provide benefits and ease of use to the people in carrying out certain activities. Technological advances aim to provide benefits and ease of use to the people in carrying out certain activities. One of them is in the financial sector, namely the creation of electronic money in as a subtitute for cash payment to assist transaction activities. In 2009, Jasa Marga together and Bank Mandiri with the support of the government cooperated to make an e-toll card as a subtitute for cash payment on toll roads. This is intended to facilitate the increasing transactions number of toll users. In addition, e-toll card can be used for other transactions. The perceived usefullness dan ease of use by customer will affect their level of satisfaction after using technology of e-toll card. This research uses quantitative research methods. The results of this study indicate that part there is not positive and significant influence between Perceived Usefulness on the E-toll Customer Satisfaction by 8,44% and there is a positive and significant influence between Ease of Use on the E-toll Customer Satisfaction by 49,56%. Simultaneously there is a positive and significant influence between Perceived Usefulness and Ease of Use on the E-toll Customer Satisfaction by 58%